Clonal Dynamics In Vivo of Virus Integration Sites of T Cells Expressing a Safety Switch - Chang, Edmund C (Mol Ther, 2016)
Safety switches are becoming relevant for the clinical translation of T-cell–based immunotherapies. In patients receiving an allogeneic hematopoietic stem cell transplant, the inducible caspase-9 gene (iC9) safety switch expressed by donor-derived T lymphocytes efficiently controls acute graft versus host disease (GvHD). However, in vivo elimination of iC9-T cells by the chemical inducer of dimerization (CID) that activates the iC9 protein is incomplete. To study this effect, we characterized the clonal diversity and dynamics of vector insertion sites (VIS) in iC9-T cells pre- and post-CID administration in four patients who developed GvHD. We identified 3,203 VIS among four patients and followed their in vivo clonal dynamics up to 161 days post-CID. VIS were categorized by their proximity to host genome elements, gene associations, and cis-modulatory relationship to mapped promoters. We found that VIS are preferentially located near open chromatin and promoter regions; furthermore, there was no evidence for selection bias among VIS surviving the CID treatment. The majority of iC9-T cells with high normalized VIS copy number at the time of GvHD onset were eliminated by CID, while iC9-T cells detectable post-CID generally have low normalized VIS copy number. We propose that suboptimal iC9 transgene expression is responsible for the incomplete elimination of iC9-T cells and illustrate here by simple model how cis-modulatory influences of local genome context and T-cell receptor activation status at time of CID treatment contribute to stochastic sparing of iC9-T cells.